Propuesta de rediseño parque Martha Bucaram de Roldós, ubicado en Puerto Baquerizo Moreno – San Cristóbal en la Islas Galápagos - Cedeño Cedeño, Luis Gregorio (2024)
The following research project located on the island of San Cristóbal Galapagos aims to redesign the Martha Bucaram de Roldos Park where new spaces or areas can be created with different activities such as sports areas, reading areas, rest areas, viewpoints, gymnastics, children's games, stage and green area where all the inhabitants of the island and tourists can enjoy the landscape and tranquility of the place. Through research that we were able to carry out with the residents of the island about the current state of the park, they made us realize how important it is to have more space and entertainment area and that is why the proposal that we are presenting is ideal for the tourist reactivation of the park and especially of the island.....